2009
DOI: 10.1007/s10295-009-0650-8
|View full text |Cite
|
Sign up to set email alerts
|

Production and optimization of cellulase-free, alkali-stable xylanase by Bacillus pumilus SV-85S in submerged fermentation

Abstract: This paper reports the production of a cellulase-free and alkali-stable xylanase in high titre from a newly isolated Bacillus pumilus SV-85S using cheap and easily available agro-residue wheat bran. Optimization of fermentation conditions enhanced the enzyme production to 2995.20 +/- 200.00 IU/ml, which was 9.91-fold higher than the activity under unoptimized basal medium (302.2 IU/ml). Statistical optimization using response-surface methodology was employed to obtain a cumulative effect of peptone, yeast extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 46 publications
6
73
2
15
Order By: Relevance
“…B. subtilis BS04 showed highest enzyme production at 35ºC. Higher incubation temperature also is 50-60ºC, which has been reported by other researchers in the literature [44][45][46][47][48][49].…”
Section: Resultssupporting
confidence: 72%
“…B. subtilis BS04 showed highest enzyme production at 35ºC. Higher incubation temperature also is 50-60ºC, which has been reported by other researchers in the literature [44][45][46][47][48][49].…”
Section: Resultssupporting
confidence: 72%
“…Thereby, we suggested the combination of yeast extract and peptone as the nitrogen source was anticipated to be the xylanase inducer for B. subtilis to produce more activity. This was supported by Nagar et al, [12] stated that organic nitrogen including yeast extract and peptone produced higher xylanase activity of 448.99 and 348.47 U/mL compared with inorganic compounds such as KNO 3 , (NH 4 ) 2 SO 4 and NaNO 3 . Additionally, Battan et al, [13] also reported that combination of yeast extract and peptone resulted in higher xylanase production.…”
Section: Resultssupporting
confidence: 67%
“…Various alkaliphilic bacteria have been shown to produce xylanase [6] with potential to remove color from paper mill effluents [19,58,171]. Other bacteria [20,178] showed production of xylanases that were adaptable to and stable at broad ranges of pH.…”
Section: Lipasementioning
confidence: 99%